‘Just because I’m vegan doesn’t mean my dog is’: exploring human-animal relations among raw meat feeders in the UK and Australia - Ciecierska-Holmes, Natalia (2025)
In food studies scholarship, food has long been recognised as a lens through which to understand human social, cultural, and ethical identities and relations. Non-human animals, when present, are often conceptualised as the ‘eaten’, with a persisting assumption that humans are the ‘eaters’. This thesis begins by challenging this assumption and instead views animals-as-eaters. Drawing on understandings of the diverse and complex relationships with non-human animals in human-animal studies research, this interdisciplinary thesis seeks to explore the role of dog food and feeding as a means of understanding human-animal relations – referred to as ‘human-dog feeding relations’. While most dogs in Western cultural contexts are fed commercial kibble diets, alternative dog diets are gaining popularity. Popular among these, even for vegan and vegetarian dog owners, are raw meat-based diets (RMBDs), consisting of fresh or uncooked ingredients from farmed or wild animals that are thought to mimic natural or ancestral diets. The phenomenon of vegan and vegetarian dog owners feeding their dogs RMBDs raises interesting questions about possible tensions between human and dog diets, especially regarding ethical and environmental values. Moreover, by foregrounding complexity and diversity in approaches to human-dog feeding relations, it challenges prevalent ideas in the fields of veterinary and consumer science research that there are increasing similarities between pet food and human food. This research employs an interpretative qualitative case-study approach to investigate the relationships of dog owners in the United Kingdom and Australia who follow plant-based diets (vegan, vegetarian, flexitarian) while feeding their dogs RMBDs. The research combines online interviews with participant-generated visual feeding diaries from 27 dog owners and their 53 dogs in the UK and Australia. The interview data was analysed using reflexive thematic analysis, resulting in the broad themes of care, control, and food identities. My analysis shows that feeding dog RMBDs is shaped by an ideology I have described as ‘intensive pet care’, which emphasises the need to nourish dogs, respond to their preferences, and meet their species-specific needs. Despite following plant-based diets themselves, participants held a strong belief that dogs need meat, which I interpret as closely tied to discourses of animality. RMBDs were also a way of establishing control over perceived contamination in the food system; while microbial risks were seen as manageable in the context of the home, chemical contamination in pet food manufacturing and production was of larger concern. Finally, food identities and resulting tensions from meat consumption were navigated through discourses I call ‘ethical (raw) meat’, which address animal welfare and sustainability. Drawing the analysis together, the thesis discusses the implications of this research for conceptually expanding research on human-dog feeding relations and conducting qualitative research with non-human animals. It also offers considerations for future research and interested parties, such as veterinary professionals, animal health and welfare organisations, and pet food regulatory bodies.